Mapping hippocampal glutamate in mesial temporal lobe epilepsy with glutamate weighted CEST (GluCEST) imaging. Issue 2 (29th September 2022) - Lucas, Alfredo; Nanga, Ravi Prakash Reddy; Hadar, Peter; Chen, Stephanie; Gibson, Adam; Oechsel, Kelly; Elliott, Mark A.; Stein, Joel M.; Das, Sandhitsu; Reddy, Ravinder; Detre, John A.; Davis, Kathryn A.
Abstract: Temporal lobe epilepsy (TLE) is one of the most common subtypes of focal epilepsy, with mesial temporal sclerosis (MTS) being a common radiological and histopathological finding. Accurate identification of MTS during presurgical evaluation confers an increased chance of good surgical outcome. Here we propose the use of glutamate‐weighted chemical exchange saturation transfer (GluCEST) magnetic resonance imaging (MRI) at 7 Tesla for mapping hippocampal glutamate distribution in epilepsy, allowing to differentiate lesional from non‐lesional mesial TLE. We demonstrate that a directional asymmetry index, which quantifies the relative difference between GluCEST contrast in hippocampi ipsilateral and contralateral to the seizure onset zone, can differentiate between sclerotic and non‐sclerotic hippocampi, even in instances where traditional presurgical MRI assessments did not provide evidence of sclerosis. Overall, our results suggest that hippocampal glutamate mapping through GluCEST imaging is a valuable addition to the presurgical epilepsy evaluation toolbox. Abstract : Our study provides, for the first time, a complete characterization of the differences in laterality and distribution of hippocampal GluCEST contrast, and consequently glutamate distribution, in both lesional and non‐lesional mesial temporal lobe (MTLe) epilepsy. We demonstrate the ability of GluCEST imaging in distinguishing these two subtypes of MTLe, even in instances where traditional structural MRI sequences failed to do so.